Antioxidant Potential of Gallic Acid Prevents Di-2-ethyhexyl Phthalate-induced Inhibition of Osteogenic Differentiation - Hussein, Abnosi Mohammad; Mahrokh, Parvaz (Current Drug Metabolism, 2025)
ObjectiveDi-2-ethylhexylphthalate (DEHP) is utilized as a plasticizer in polyvinylchloride products (PVC). When medical devices like blood bags, tubes, and syringes are employed, DEHP leaches out of the PVC polymers and enters biological fluids through non-covalent binding. The presence of DEHP in peripheral blood leads to contamination of bone marrow. Previous research has demonstrated that this chemical induces oxidative stress, which adversely affects the viability and osteo-differentiation of bone marrow mesenchymal stem cells (BMSCs). Hence, our current study aims to utilize gallic acid (GA), a natural antioxidant, to alleviate the inhibitory effects of DEHP on BMSCs' osteogenic differentiation.Materials and MethodsIn osteogenic media, BMSCs extracted from Wistar rats were treated with 0.25 μM of GA and 100 μM of DEHP individually and in combination for 20 days. Then viability, total protein, malondialdehyde (MDA), total antioxidant capacity (TAC), catalase (CAT) and superoxide dismutase (SOD), alkaline phosphatase activity, production of collagen1A1 protein as well as expression of Bmp2 and 7, Smad1, Runx2, Oc, Alp, Col-1a1 genes were investigated.ResultsThe viability and differentiation ability of BMSCs was significantly (p<0.0001) decreased by DEHP, while GA significantly (P<0.0001) ameliorated the effect of DEHP. DEHP caused a significant decrease (P<0.0001) in the total protein and collagen-1A1 concentration, TAC and activity of antioxidant enzymes, but significantly (P<0.001) increased MDA level. In addition, DEHP caused a significant decrease in the expression of osteo-related genes. In the co-treatment group, GA mitigated the toxic effects of DEHP compared to the control group by inhibiting DEHP-induced oxidative stress and enhancing cell viability and osteo-differentiation properties.ConclusionThese results confirm that GA reduces the negative effects of DEHP on the osteo-differentiation of BMSCs at the cellular level. However, further studies are necessary to validate these findings.
Keywords: bone marrow